Verbalizing the symbol: Blazoning in the national heraldry of the post-soviet republics - Vorkachev, Sergey Grigorievich (Жанры речи, 2022)
The article deals with the linguistic embodiment of national symbols. On the basis of lexicography, the author determines the semantic structure of the national idea and describes its implementation in the heraldic symbols of the countries of the former USSR. The semantics of the state contains the following semantic blocks: power, territory, population (people) and the country as a whole. It is established that the main symbols of power amid artifacts are the crown, sword, scepter, orb and trident, and amid the images of fauna – images of a lion, an eagle and a griffin. The territory is symbolized through the image of the administrative and historical division of the country, images of typical representatives of its flora and fauna. Most frequently, on the coats of arms one can see images of the economically most important or most typical representatives of the country’s flora, followed by landscape elements, and only after them the images of the animal world. The symbols associated with the people inhabiting the country of the certain coat of arms include images of specifically national artifacts, objects of material culture. A significant part of the images of the national heraldry symbolizes the concepts and ideals common to the country of the coat of arms as a whole: mythological and folklore images, confessional and astronomical symbols, history and other symbols. National anthems and national heraldry coincide in the history and geography of the country, while the latter is practically lacunary in relation to the emotional and evaluative side of patriotism.